UPDATING THE INTRASPECIFIC CLASSIFICATION OF CULTIVATED FLAX (LINUM USITATISSIMUM L.) USING METHODS OF CLASSICAL GENETICS - S. N. Kutuzova; I. G. Chukhina (Труды по прикладной ботанике, генетике и селекции, 2018)
The proposed classification system of the species Linum usitatissimum L. is based on the study of morphological features and the results of analyzing hybrids from diallelic crosses among all supposed flax taxa including primitive forms and the wild species L. angustifolium Huds. Genetic similarity between taxa was judged by their morphological affinity, crossability both among themselves and with L. angustifolium as a supposed ancestor of cultivated flax, and viability of Fi reported earlier (Kutuzova, 20ll). Research results show that fiber, intermediate and crown flax forms are varieties of cultivated flax, not subspecies, as N. M. Chernomorskaya and A. K. Stankevich (1987) claimed. New flax varieties have been described: L. usitatissimum subsp. usitatissimum var. nanum Kutuz. var. nova, dwarf flax from Ethiopia differing from other crown forms in that its F1 from the cross with L. angustifolium is practically unviable, and L. usitatissimum subsp. bienne (Mill.) Stankev. var. colchicum Kutuz. var. nova. - Colchian flax.